Open-source customizable website to follow-up physical rehabilitation of cardiovascular patients at home - Sabala, Ariadna; Mcbrearty, Donough; Salama, Raffaella; Farré, Ramon; Loughnane, Ailís; Otero, Jorge; Farré, Núria (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTelemedicine home monitoring of physical rehabilitation in cardiovascular patients, which may substantially improve adherence and, thus, prognosis and quality of life, is an underused practice. Indeed, the Apps and websites available are generic and cannot be easily adapted to each specific rehabilitation protocol. We thus aimed at developing a flexible, low-cost, and open-source telemedicine tool that can be customized and operated by any healthcare professional with just user-level internet knowledge.MethodsThe website was co-designed by an interdisciplinary team, including website developers and clinical experts in physical rehabilitation programs for patients with cardiovascular diseases. The operability and robustness of the website were tested on simulated patients and health professionals, and the suitability of the tutorial for website customization was assessed.ResultsThe website asks the patient to complete a periodic diary of physical activities (e.g., intensity, type, duration, warm-up, cool-down, subjective effort). At any time, the patient can see graphs of the different types of exercise performed during a selected period. The website allows healthcare professionals to browse patients’ data, send feedback messages, and export data in a conventional spreadsheet format. The tutorial for website customization was prepared as a learning by doing tool.ConclusionsThe website developed can interest cardiovascular physical rehabilitation professionals aiming at quickly and cheaply setting up an approach for home monitoring programs. This telemedicine tool can also be customized to different clinical applications and is particularly well suited for low-resource settings.